A POLYNOMIAL ANALOGUE OF LANDAU'S THEOREM AND RELATED PROBLEMS. Issue 2 (5th June 2017) - Gorodetsky, Ofir
Abstract : Recently, an analogue over $\mathbb{F}_{q}[T]$ of Landau's theorem on sums of two squares was considered by Bary-Soroker, Smilansky and Wolf. They counted the number of monic polynomials in $\mathbb{F}_{q}[T]$ of degree $n$ of the form $A^{2}+TB^{2}$, which we denote by $B(n, q)$ . They studied $B(n, q)$ in two limits: fixed $n$ and large $q$ ; and fixed $q$ and large $n$ . We generalize their result to the most general limit $q^{n}→ ∞$ . More precisely, we prove $$\begin{eqnarray}B(n, q)\sim K_{q}· \binom{n-\frac{1}{2}}{n}· q^{n}, \quad q^{n}→ ∞, \end{eqnarray}$$ for an explicit constant $K_{q}=1+O(1/q)$ . Our methods are different and are based on giving explicit bounds on the coefficients of generating functions. These methods also apply to other problems, related to polynomials with prime factors of even degree.